Exploring alternative biomarkers of pesticide pollution in clams - Solé, Montserrat (2020)
Acetylcholinesterase (AChE) is a reliable biomarker of pesticide exposure although in clams this activity is often very low or undetectable. Carboxylesterases (CEs) exhort several physiological roles, but also respond to pesticides. Searching for an AChE alternative, baseline CE activities were characterised in Ruditapes decussatus gills and digestive glands using five substrates suggestive of different isozymes. The long chain p-nitrophenyl butyrate and 1-naphthyl butyrate were the most sensitive. In the digestive gland, their kinetic parameters (Vmax and Km) and in vitro sensitivity to the organophosphorus metabolite chlorpyrifos oxon (CPX) were calculated. IC50 values, in the pM–nM range, suggest a high protection efficiency of CE-related enzymes towards CPX neurotoxicity. Other targeted enzymes were: activities of glutathione reductase, glutathione peroxidase, catalase, glutathione S-transferases (GSTs) and lactate dehydrogenase in gills and digestive glands. The high GSTs activity and CE/AChE ratio suggests that R. decussatus has a great capacity for enduring pesticide exposure.